Deviancy, Dependency, and Disability: The Forgotten History of Eugenics and Mass Incarceration - Riseby, Emil (2015)
Three widely discussed explanations of the punitive carceral state are racism, harsh drug laws, and prosecutorial overreach. These three narratives, however, only partially explain how our correctional system expanded to its current overcrowded state. Neglected in our discussion of mass incarceration is our largely forgotten history of the long-term, wholesale institutionalization of the disabled. This form of mass detention, motivated by a continuing application of eugenics and persistent class-based discrimination, is an important part of our history of imprisonment, one that has shaped key contours of our current supersized correctional system. Only by fully exploring this forgotten narrative of long-term detention and isolation will policy makers be able to understand, diagnose, and solve the crisis of mass incarceration